Computerized systems and databases for pharmacovigilance in Russia - B. K. Romanov; E. N. Saykina; E. Yu. Baidikova; U. M. Shirokova; E. D. Shchukin (Реальная клиническая практика: данные и доказательства)
The results of identifying new risks for pharmacovigilance systems and databases in Russia, including the Roszdravnadzor's web-based pharmacovigilance system, are presented. The lack of information in the database on pharmacovigilance of the Eur asian Economic Union and problems with updating programs and using alternative systems were noted. Changes in RWD/RWE information in global pharmacovigilance over the past 5 years.Objectives. Identification of new risks associated with pharmacovigilance systems and databases in Russia. Materials and methods. The materials were obtained by interviewing 138 pharmacovigilance specialists and from regula tory legal acts, publications, computerized systems, and databases through open and authorized access. Sociological methods were used: survey in Telegram-group «Pharmacovigilance CIS» in October 2024 and information-analytical methods: user testing, review, and analysis of Russian and foreign systems and programs, including databases for pharmacovigilance, regu latory documentation, and bibliography.Results. 17 % of pharmacovigilance specialists use exclusively Russian software in their computerized systems and data bases, 29 % use only foreign software, 35 % use both Russian and foreign software, and 19 % find it difficult to classify their systems and programs as domestic or foreign. The results of user testing indicate that there are problems and risks with access ing Roszdravnadzor’s web-based pharmacovigilance system via foreign browsers in current versions of Windows, Android, MacOS, iOS, and Unix operating systems. The unified pharmacovigilance database of the Eurasian Economic Union as of No vember 5, 2024, contains no public access notifications. The composition of data in the global database, VigiBase, has changed over 5 years: the largest number of cases now relates to COVID-19 vaccines. Russian data were not included in EudraVigilance and VigiBase (from October 10, 2020), which does not allow them to be considered in the global analysis.Conclusion. New potential risks for computerized systems and databases for pharmacovigilance in Russia have been iden tified — loss of data and reduction in the quality of analysis.